Implementation of Islamic Communication in Therapeutic Communication in Midwives - S. Dinar Annisa Abdullah (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2023)
This study aims to describe the Implementation of Islamic Communication in Therapeutic Communication to Midwives at Inche Abdoel Moeis Hospital Samarinda. This research is a qualitative descriptive study with a phenomenological approach. The results showed that there were six therapeutic communication techniques applied by midwives at Inche Abdoel Moeis Samarinda Hospital, namely (1) active and attentive listeners, (2) showing acceptance, (3) conveying the results of observations, (4) giving appreciation, (5) assertiveness, and (6) humor. Meanwhile, Islamic communication in therapeutic communication to midwives at RSUD Inche Abdoel Moeis Samarinda has yet to be formally applied but substantially has similarities in the principles of Islamic communication. This is manifested in the principles of (1) the principle of honesty, (2) positive speech principle, (3) the principle of the package (heart, verbal, and deed), (4) the principle of two ears and one mouth, (5) the principle of mutual influence, (6) the principle of privacy